Control of aging by the renin–angiotensin system: a review of C. elegans, Drosophila, and mammals - Egan, Brian M.; Scharf, Andrea; Pohl, Franziska; Kornfeld, Kerry (Frontiers in Pharmacology, 2022)
The free-living, non-parasitic nematode Caenorhabditis elegans is a premier model organism for the study of aging and longevity due to its short lifespan, powerful genetic tools, and conservation of fundamental mechanisms with mammals. Approximately 70 percent of human genes have homologs in C. elegans, including many that encode proteins in pathways that influence aging. Numerous genetic pathways have been identified in C. elegans that affect lifespan, including the Dietary Restriction (DR) pathway, the Insulin/insulin-like growth factor (IGF) signaling pathway, and disruption of components of the mitochondrial electron transport chain. C. elegans is also a powerful system for performing drug screens, and many lifespan-extending compounds have been reported; notably, several FDA-approved medications extend lifespan in C. elegans, raising the possibility that they can also extend lifespan in humans. The renin-angiotensin system (RAS) in mammals is an endocrine system that regulates blood pressure and a paracrine system that acts in a wide range of tissues to control physiological processes; it is a popular target for drugs that reduce blood pressure, including angiotensin-converting enzyme (ACE) inhibitors and angiotensin II receptor blockers (ARBs). Emerging evidence indicates this system influences aging. In C. elegans, decreasing activity of the ACE homolog acn-1 or treatment with the ACE-inhibitor Captopril significantly extends lifespan. In Drosophila, treatment with ACE inhibitors extend lifespan. In rodents, manipulating the RAS with genetic or pharmacological interventions can extend lifespan. In humans, polymorphisms in the ACE gene are associated with extreme longevity. These results suggest the RAS plays a conserved role in controlling longevity. Here, we review studies of the RAS and aging, emphasizing the potential of C. elegans as a model for understanding the mechanism of lifespan control.